ANALISIS DESKRIPTIF MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM UPAYA PENINGKATAN MOTIVASI BELAJAR - Yurike Yurike; Wahyudi Wahyudi (STKIP Andi Matappa, 2020)
Motivation to learn is an encouragement that triggers students to learn so that the learning process leads to the goals to be achieved. Without motivation in students, the learning objectives are difficult to achieve. The type of jigsaw cooperative learning model aims to increase students' thinking power, a higher sense of responsibility and curiosity. The jigsaw cooperative learning model is a group learning system that pays attention to equity such as gender and intellectuality. Each group member needs each other and has the responsibility of mastering the material with the expert group and presenting the results of the discussion to the home group then they take turns with other group members. The responsibility for mastering the material for each individual will encourage students to learn in order to master the material. The type of data collection in this research is literature review which aims to find out how the jigsaw cooperative learning model is used to increase motivation to learn mathematics. Data collection techniques were obtained from several relevant sources related to the research being studied. From several sources obtained, it is stated that the results of research on the application of the type of jigsaw cooperative learning model in classroom learning activities can help students increase learning motivation